Exploring the normative context for women's entrepreneurship in Pakistan: a critical analysis. Issue 2 (30th May 2018) - Roomi, Muhammad Azam; Rehman, Sumaira; Henry, Colette
Abstract : Purpose: The role of women in Pakistani society – largely embedded in its patriarchal socio–cultural environment – has important implications for women's entrepreneurial activity in the country. This study aims to investigate and analyse the influence of informal institutional factors on women's entry into entrepreneurship in Pakistan, and determine how women exercise agency to cope with the constraints posed by such factors. Design/methodology/approach: A qualitative approach is used to explore the normative context and lived experiences of women entrepreneurs in relation to the influence of socio–cultural beliefs and attitudes on their entrepreneurial career choices. Findings: The findings suggest that women's entrepreneurial career choices both revolve around and are shaped by a complex interplay of socio–cultural influences. Pakistani women entrepreneurs exercise their agency as a means of negotiating gender roles within both household and society, using religious descriptions as a means to justify their entrepreneurial activity. Research limitations/implications: While every effort has been made to ensure that the data were objectively interpreted, and the derived findings were robustly analysed, the research team acknowledges the many difficulties associated with adopting a social constructionist approach. As articulated by Fletcher (2011), the key issues of contextual objectivity (i.e. where the researcher judges what is important), reflexive turn (the need for the researcher to constantly reconnect with the subject) and potential multiplicity of contexts (the various contextual and potentially conflicting influences on the researcher) presents ongoing challenges for researchers in this field. Originality/value: This study offers valuable insights into the impact of the informal (socio–cultural) institutional factors on women's entrepreneurial activity, opening up new avenues for further research. The study also contributes to the women's entrepreneurship literature from the perspective of an Islamic developing country.